Volumetric 3-Dimensional Analysis of the Supraorbital vs Pterional Approach to Paramedian Vascular Structures: Comprehensive Assessment of Surgical Maneuverability. Issue 2 (February 2022) - Houlihan, Lena Mary; Abramov, Irakliy; Loymak, Thanapong; Jubran, Jubran H.; Staudinger Knoll, Ann J.; Farhadi, Dara S.; Naughton, David; Howshar, Jacob T.; O'Sullivan, Michael G. J.; Lawton, Michael T.; Preul, Mark C.
Abstract : BACKGROUND: Both the pterional and supraorbital approaches have been proposed as optimal access corridors to deep and paramedian anatomy. OBJECTIVE: To assess key intracranial structures accessed through the surgical approaches using the angle of attack (AOA) and the volume of surgical freedom (VSF) methodologies. METHODS: Ten pterional and 10 supraorbital craniotomies were completed. Data points were measured using a neuronavigation system. A comparative analysis of the craniocaudal AOA, mediolateral AOA, and VSF of the ipsilateral paraclinoid internal carotid artery (ICA), terminal ICA, and anterior communicating artery (ACoA) complex was completed. RESULTS: For the paraclinoid ICA, the pterional approach produced larger craniocaudal AOA, mediolateral AOA, and VSF than the supraorbital approach (28.06° vs 10.52°, 33.76° vs 23.95°, and 68.73 vs 22.59 mm 3 normalized unit [NU], respectively; P < .001). The terminal ICA showed similar superiority of the pterional approach in all quantitative parameters (27.43° vs 11.65°, 30.62° vs 25.31°, and 57.41 vs 17.36 mm 3 NU; P < .05). For the ACoA, there were statistically significant differences between the results obtained using the pterional and supraorbital approaches (18.45° vs 10.11°, 29.68° vs 21.01°, and 26.81 vs 16.53 mm 3 NU; P < .005). CONCLUSION: The pterional craniotomy was significantly superior in all instrument maneuverability parameters for approaching the ipsilateral paraclinoid ICA, terminal ICA, and ACoA. This global evaluation of 2-dimensional and 3-dimensional surgical freedom and instrument maneuverability by amalgamating the craniocaudal AOA, mediolateral AOA, and VSF produces a comprehensive assessment while generating spatially and anatomically accurate corridor models that provide improved visual depiction for preoperative planning and surgical decision-making.